Memahami Tanda-Tanda Zaman Sering Terjadi Dalam Kehidupan Manusia Pada Masa Kini - Alfin susanto zagoto; Aprianus Lendrik Moimau (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
This research identifies and analyzes various sources and references for one's critical understanding in increasing one's narrow understanding in understanding the signs of the times. Christians' understanding of the end times always refers to a number of signs which are considered to indicate that the end times are approaching. In general, in the Christian view, the end times will begin with the second coming of Jesus accompanied by the destruction of the world and God's judgment on humans. a number of signs that will occur before the end of time. For example, in Matthew 24, Jesus speaks of war, famine, earthquakes, and apostasy as signs of the end times. However, in daily life, the Bible also emphasizes the importance of living alertly and prepared. In Matthew 24:42-44, Jesus teaches to always be on the alert because His coming is unknown. This understanding emphasizes that even though the signs of the end times may seem clear, the main focus for believers is living according to Christ's teachings, keeping the faith , and always ready to welcome His arrival.